Remote laboratories and inclusive education: A symbiosis for diversity and social empowerment - Andrade-Sánchez, Fernando; Muñoz-Melguizo, Carlos Andrés; Vasquez-Raigoza, Francisco Javier; Villa-Tavera, Yeny Lucía (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Academic discussions on education have been strengthened on multiple occasions by concepts from other disciplines or fields, in this way, this article explores the symbiotic potential of remote laboratories with inclusive education through a survey of the Latin American literature around these categories, as well as their possible didactic uses, since, thanks to its interactive and culturally flexible characteristics, this conceptual meeting is made with the aim of strengthening the processes of emancipation and social empowerment from historically excluded groups.